2013
DOI: 10.3389/fmicb.2013.00002
|View full text |Cite
|
Sign up to set email alerts
|

Technological and probiotic potential of BGRA43 a natural isolate of Lactobacillus helveticus

Abstract: Lactobacillus helveticus BGRA43 is a human intestinal isolate showing antimicrobial activity, amongst others, against Yersinia enterocolitica, Shigella sonnei, Shigella flexneri, and Streptococcus pneumoniae. BGRA43 produces PrtH proteinase with proteolytic activity on both casein and β-lactoglobulin (BLG). BGRA43 is able to reduce the allergenicity of BLG. Bioactive peptides released in BGRA43 fermented milk are potent modulators of innate immunity by modulating the production of proinflammatory cytokines IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…For this reason, probiotic bacteria should survive at 0.15–0.30% bile acid . The excellent ability to remain viable in stimulated gastric juice and good bile tolerance of L. helveticus PJ4 and L. plantarum PJ7 are in accordance with previous results . This finding suggests that these isolates have the potential to survive in the human GI tract and can likely survive the passage through the stomach and small and large intestine.…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, probiotic bacteria should survive at 0.15–0.30% bile acid . The excellent ability to remain viable in stimulated gastric juice and good bile tolerance of L. helveticus PJ4 and L. plantarum PJ7 are in accordance with previous results . This finding suggests that these isolates have the potential to survive in the human GI tract and can likely survive the passage through the stomach and small and large intestine.…”
Section: Discussionsupporting
confidence: 89%
“…L. helveticus has been reported to have an efficient proteolytic system (Griffiths and Tellez ). It is well known that the proteolytic activity of lactobacilli, in terms of the degradation of casein fractions, plays an important role in the development of texture and flavor during the fermentation process (Strahinic and others ). Therefore, L. helveticus starters are widely used in the manufacture of fermented milk beverages and hard cheeses (Giraffa and others ; Beresford and others ; Rossettia and others ).…”
Section: Discussionmentioning
confidence: 99%
“…The research efforts in this area are continuing and some promising results were reported for yeasts species isolated from olives such as C. boidinii , C. oleophila , D. hansenii , and P. membranifaciens to have a potential (Psani and Kotzekidou, 2006; Silva et al, 2011; Arroyo-López et al, 2012a). The main criteria for probiotic selection documented by FAO/WHO, (2002, 2006) is being used as a guideline by a number of researchers to evaluate the probiotic potential of bacteria and yeasts (Morrow et al, 2012; Peres et al, 2012; Strahinic et al, 2012; Argyri et al, 2013). These criteria include; the survival of bacterial cells during their passage through the gastrointestinal tract and the ability of a strain to colonize transiently mucosa (Guarner et al, 2005; Argyri et al, 2013).…”
Section: Probiotic Characteristics Of Starter Culturesmentioning
confidence: 99%